Evaluation of acetabular cup initial fixation by using resonance frequency principle - Henys, Petr; Capek, Lukas; Fencl, Jaroslav; Prochazka, Egon (Proceedings of the Institution of Mechanical Engineers. Part H, Journal of Engineering in Medicine, 2015)
The clinical practice shows that the loosening of acetabular cups is more frequent than stem loosening. With standard cups, the incidence of dislocation failure is highest in the first year after arthroplasty implantation. The aim of the study was to quantitatively evaluate the implant-bone stability of a cementless acetabular cup prosthesis by using a device based on resonance frequency analysis. The evaluation of this device was done by finite element analysis and in vitro experiments. It was shown that not all the resonance frequencies can be measured by our device. The resonance frequencies vary within the range of 500-3000 Hz. The proposed power spectrum measurement gives the information about the absolute stiffness of the press-fit implant.
Keywords: Finite Element Analysis; Equipment Failure Analysis; Sensitivity and Specificity; senzitivita a specificita; Oscillometry; Acetabulum; Humans; protetické vybavení; lidé středního věku; Computer Simulation; Arthroplasty, Replacement, Hip; Models, Biological; modul pružnosti; náhrada kyčelního kloubu; lidé; vibrace; reprodukovatelnost výsledků; Hip Prosthesis; Elastic Modulus; Stress, Mechanical; počítačová simulace; Male; Reproducibility of Results; Middle Aged; Prosthesis Fitting; Vibration; biologické modely; acetabulum; kyčelní protézy; mužské pohlaví; analýza selhání vybavení; oscilometrie; analýza metodou konečných prvků; mechanický stres